2006
DOI: 10.1007/s11556-006-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Regular physical exercise in patients with type II diabetes mellitus

Abstract: It is widely accepted that regular physical exercise helps diabetic patients control blood glucose, reduce cardiovascular risk factors, and prevent other related complications. In spite of the undoubted benefits of regular physical exercise, diabetic patients with chronic complications should be aware of potential hazards of practicing exercise. To avoid some harmful consequences of acute exercise, it is necessary to adopt a vigilant attitude with these risk patients and to carefully adjust type and intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
1
9
0
1
Order By: Relevance
“…It was found that aged rats developed an increase in insulin resistance represented by, significant elevation of serum glucose, serum insulin and HOMA-IR index. This finding is in agreement with previous observations [41,42] . Swim exercise training for 6 weeks was seen to reverse insulin resistance induced by aging in rats.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that aged rats developed an increase in insulin resistance represented by, significant elevation of serum glucose, serum insulin and HOMA-IR index. This finding is in agreement with previous observations [41,42] . Swim exercise training for 6 weeks was seen to reverse insulin resistance induced by aging in rats.…”
Section: Discussionsupporting
confidence: 94%
“…70 Exercise is used for the prevention, 71 and treatment of T2DM [72][73][74][75][76][77][78] by improving glycemic control. 43,[79][80][81][82][83][84][85][86] It is a comprehensive element of diabetes management. 87,88 A randomized trial has reported that exercise performed for 30 minutes after meal eating may provide better improvements in glycemic control for people with T2DM.…”
Section: Management Of T2dmmentioning
confidence: 99%
“…160 Further, evidence has shown that PA leads to an improvement in insulin action. 70,85,[162][163][164] This improvement in insulin action involves an enhanced sensitivity, and responsiveness of peripheral glucose uptake probably by muscle to insulin and also an increased inhibition of hepatic glucose production by insulin. 163 Besides, the improved insulin action involves glucose transport, glycogen synthesis, and glycogen synthase activation as well as amino acid transport.…”
Section: The Physiological Effects Of Physical Activity In T2dmmentioning
confidence: 99%
“…Aging constitutes an important risk factor for insulin resistance and development of type 2 diabetes mellitus . The ability to control the blood glucose level declines during the life span and phenotype modifications in skeletal muscle, the major site for glucose disposal, seem to play an important role in this decline .…”
Section: Introductionmentioning
confidence: 99%
“…Aging constitutes an important risk factor for insulin resistance and development of type 2 diabetes mellitus. 28,35 The ability to control the blood glucose level declines during the life span 18,21,30 and phenotype modifications in skeletal muscle, the major site for glucose disposal, seem to play an important role in this decline. 13,38 In rodents, a progressive decline in skeletal muscle glucose uptake, in the absence and in the presence of insulin, was observed during the phase of growth related to weight gain, between the first and fourth months of age.…”
Section: Introductionmentioning
confidence: 99%